Quality measures for primary mental healthcare: a multistakeholder, multijurisdictional Canadian consensus. Issue 6 (10th August 2010) - Waraich, Paul; Saklikar, Renée Sarojini; Aubé, Denise; Jones, Wayne; Haslam, David; Hamill, Karen
Abstract : Objective: To develop quality measures using a consensus-based, multistakeholder process to improve delivery of mental health services within primary healthcare settings. Methods: A three-stage consensus model culminating in a two-round, modified Delphi postal survey ranking quality measures according to 'actionability, ' relevance and overall importance. Participants: More than 800 people from all 10 provinces and three territories in Canada participated in the study, representing consumers/advocates, clinicians, academics and government decision-makers from regional, provincial and federal levels. A small group with expertise in First Nations and rural-setting health issues was also included, as well as international experts. Results: The top overall pan-Canadian measure was 'Education about Depression.' 'Actionability' was a key criterion for many of the top 30 measures. Fifty per cent of these measures focused on three major themes: depression, self-harm and access to a broader spectrum of treatment (such as outreach services and psychotherapy). Additional themes included the need for greater collaboration, respectful treatment of patients and families, and improved evaluation of patients. One-way ANOVA results indicated statistically significant differences (p <0.05) between academics, clinicians, consumers and decision-makers on approximately 5% of quality measure ratings. The majority (85% of the 5%) of these differences involved consumer stakeholders. Conclusion: A small set of specific consensus measures were identified through a rigorous, evidence-informed process. These measures can be used for system-wide changes or at the individual practice level. Although these measures have been developed within a Canadian context, the methodology utilised and the measures selected can be adapted elsewhere.